A Sufficient Condition for the Uniform Convergence of Truncated Cardinal Functions Whittaker Inside the Interval (Global Journal of Science Frontier Research, 2017)
In terms of the one-sided module of continuity and positive (negative) module of change obtain sufficient conditions for the uniform convergence of truncated cardinal functions Whittaker inside the interval.
Keywords: sinc approximation; interpolation functions; uniform approximation; cardinal functions Whittaker